2020
DOI: 10.1101/2020.03.06.981175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association Study based on Topological Constraints of Protein-Protein Interaction Networks

Abstract: The non-random interaction pattern of a protein-protein interaction network (PIN) is biologically informative but its potentials have not been fully utilized in omics studies. Here, we propose a network-permutation-based association study (NetPAS) method that gauges the observed interactions between two sets of genes based on the comparison between permutation null models and the empirical networks. This enables NetPAS to evaluate relationships, constrained by network topology, between gene sets related to dif… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 52 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Similar method had been previously applied to a smaller yeast PIN and observed that the high-degree, hub proteins tend to avoid interactions with the other hub proteins, which was suggested to contribute to the stability of the PIN (Maslov and Sneppen 2002). This approach had been recently applied to estimate the association strengths between different categories of proteins using a human PIN (Guo and Qin 2020). Figure 5 shows the global landscape in the variable spaces of node degrees and RLS ratios of single-gene deletion mutations.…”
Section: A Proteome-wide Protein Interaction Probability Landscapementioning
confidence: 92%
See 2 more Smart Citations
“…Similar method had been previously applied to a smaller yeast PIN and observed that the high-degree, hub proteins tend to avoid interactions with the other hub proteins, which was suggested to contribute to the stability of the PIN (Maslov and Sneppen 2002). This approach had been recently applied to estimate the association strengths between different categories of proteins using a human PIN (Guo and Qin 2020). Figure 5 shows the global landscape in the variable spaces of node degrees and RLS ratios of single-gene deletion mutations.…”
Section: A Proteome-wide Protein Interaction Probability Landscapementioning
confidence: 92%
“…22,188 null network models were built in a way such that all vertices were randomly reshuffled, yet the node degrees preserved as the original PIN. We term these null models the MS02 null models (Maslov and Sneppen 2002;Qin et al 2003;Guo and Qin 2020).…”
Section: Protein-protein Interaction Network and Random Null Network mentioning
confidence: 99%
See 1 more Smart Citation